2000
DOI: 10.2486/indhealth.38.62
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Problems in White-Collar Male Workers in an Electric Equipment Manufacturing Company in Japan.

Abstract: In order to clarify poor sleep habits and prevalence in sleep problems (disturbances) of healthy male white-collar workers and the relationship of these to age and job type, a total of 1,161 Japanese employees of an electric equipment manufacturing company (aged 23 to 59, mean 37 years) were surveyed by means of a mailed questionnaire. The workers were asked about eleven sleep habits. They were also divided into four groups according to age and job type: 23-29 (n=226), 30-39 (n=597), 40-49 (n=225) and 50-59 (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 23 publications
1
33
1
Order By: Relevance
“…Nakata et al 50) found no significant differences in sleep problems amoung job categories, except for sleep insufficiency. In their study, clerical workers had a prevalence of definite insufficiency of sleep of 1.5%, whereas the prevalence was between 7.2% to 8.7% in other groups of workers (managerial, technical).…”
Section: Studies On Working Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…Nakata et al 50) found no significant differences in sleep problems amoung job categories, except for sleep insufficiency. In their study, clerical workers had a prevalence of definite insufficiency of sleep of 1.5%, whereas the prevalence was between 7.2% to 8.7% in other groups of workers (managerial, technical).…”
Section: Studies On Working Populationmentioning
confidence: 99%
“…There are few studies about the prevalence of insomnia at the workplace [44][45][46][47][48][49][50][51][52][53][54][55][56] . Several occupational factors may have an impact on sleep: the work schedules, the physical environment at work (noise, heat, light) 54) and the occupational stresses (mental load, working organisation, stress) 57) , however it is difficult to evaluate the weight of working conditions in the appearance and in the development of sleep disturbances, more especially as it is well admitted that the natural history of insomnia depends on predisposing factors and of precipitating factors 58) .…”
Section: Studies On Working Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep problems have been linked to a variety of physical and mental health-related outcomes (Nakata et al, 2000;NHLBIWG, 1999;Edell-Gustafsson, Kritz, & Bogren, 2002). A recent meta-analysis demonstrated relationships between sleep problems and the risk of myocardial infarction as well as coronary heart disease, concluding that the magnitude of these associations rival those of more conventional risk factors (Schwartz, Anderson, Cole, Cornoni-Huntley, Hayes, & Blazer, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been conducted in Japan (Doi, 2005;Doi et al, 1999;Nakata et al, 2004;Nakata et al, 2000;Ota et al, 2005;Sekine et al, 2006;Utsugi et al, 2005), Finland (Urponen, Vuori, Hasan, & Partinen, 1988), Sweden (Linton, 2004), Germany (Frese & Harwich, 1984), Belgium (Pelfrene et al, 2002), and France (Ribet & Derrienic, 1999). There may be international differences in the significance and magnitude of associations due to variations in cultural contexts.…”
Section: Introductionmentioning
confidence: 99%